Large Versus Small Gastric Pouch for Roux-en-Y Gastric Bypass in Individuals With Type 2 Diabetes and a Body Mass Index < 35 kg/m2: Six-Year Outcomes - Gao, Xiang; Dai, Song; Wang, Guohui; Li, Weizheng; Song, Zhi; Su, Zhihong; Zhu, Shaihong; Zhu, Liyong; Li, Pengzhou (Frontiers in Endocrinology, 2022)
Background: Roux-en-Y gastric bypass (RYGB) results in extraordinary weight loss and glycemic control outcomes for patients with obesity; however, the effect of gastric pouch size is still unclear, and the reported results are contradictory. Additionally, long-term data on type 2 diabetes (T2D) patients with low body mass index (BMI) are sparse. This study was to assess the effect of 6-year outcomes in Chinese patients with T2D and a BMI < 35 kg/m2 who underwent RYGB with gastric pouches of different sizes. Methods: A retrospective study was performed. There were 42 patients in the large gastric pouch group (L) and 53 patients in the small gastric pouch group (S). Baseline demographic history, pre- and postoperative BMI, waist circumference, and glucose- and lipid metabolism-related indicators were compared. Results: Assessments were completed in 100%, 100%, 93.6%, and 89.4% of patients at baseline, 1 year, 3 years, and 6 years, respectively. At 6 years, the changes in BMI and fasting plasma glucose were greater in the S group (-4.25±0.51 kg/m2 and -4.58±0.73 mmol/l) than in the L group (-2.06±0.48 kg/m2 and -2.64±0.61 mmol/l). The independent predictors of complete remission of T2D were preoperative BMI and the size of the gastric pouch. A large gastric pouch was associated with a higher risk for marginal ulcers. Conclusions: A small gastric pouch results in better weight loss and glycemic control. High preoperative BMI and a small gastric pouch are associated with better T2D remission rates. A large gastric pouch leads to a higher incidence of marginal ulcers.